EFEK ESTROGENIK FRAKSI ETIL ASETAT UMBI BENGKOANG (Pachyrrhizus erosus (L.) Urb.) TERHADAP KADAR KOLESTEROL DARAH DAN TULANG PADA TIKUS Sprague Dawley TEROVARIEKTOMI - , FRANSISKA LEVIANA, S.Farm., Apt., Dr. Arief Nurrochmad, M.Si., M.Sc, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Incidence of cardiovascular diseases and osteoporosis was increased in menopausal women. Long-term use of hormone replacement therapy to solve the health problems of menopausal women could cause side effects. Therefore, it is necessary alternative agent that relatively safer to use. Bengkoang tubers (Pachyrrhizus erosus (L) Urb.) contained isoflavonoid, a compound known to have estrogenic effects. The aim of this research is to analyze the (8,9)- furanylpterocarpan-3-ol as a marker compound in the ethyl acetate fraction of Pachyrrhizus erosus (L) Urb.)âs tuber (EPE) and investigate the estrogenic effects of EPE on cholesterol levels and bone in an ovarietomized rats. The ethyl acetate fractions were analyzed the (8,9)-furanylpterocarpan-3- ol as a marker compound by HPLC. Then estrogenic effects of the fractions were tested by in vivo method. Thirty 50-days-old female SpragueâDawley rats were randomly assigned to six groups as followed, sham-operated, OVX, OVX- Estradiol (2 Âµg/day), OVX-EPE 200 mg/kgBW, OVX-EPE 400 mg/kgBW, OVX- EPE 800 mg/kgBW for 4 weeks. After treatment, urine, boold, and femur were collected. Body and uterine weight were measured. Total cholesterol, HDL and LDL cholesterol level were measured. Bone was analized for length, density, and mineral content (calcium and phosphorus). Calcium and phosphorus level on blood and urine and alkaline phosphatase also were measured. Data were analized by oneway ANOVA test, followed Duncan test (P<0,05). The results showed that the ethyl acetate fraction of EPE contained (8,9)- furanylpterocarpan-3-ol as a marker compound at 2.63 Â± 0.01% determined by HPLC. The administration EPE has estrogenic effect on cholesterol level and bone in OVX rats. EPE could decrease significantly the total cholesterol level in OVX rats. The estrogenic effects EPE to bone were described in increased bone density, and mineral content of calcium and phosphorous in bone ash. The femur mechanical testing significantly increased the ultimate load and stiffness of femurs of ovariectomized-rats that its effect was greater than OVX or shamoperated rats. Increased bone density may lead to enhanced bone strength, reducing the risk of fracture, which is evident in the administration of EPE due to high content of mineral density and content and increase the ultimate load. This study suggests a possible role of the ethyl acetate fraction of Pachyrrhizus erosus (L.).Urb. as potential alternative therapy for the treatment of health problems in post-menopausal women because of its beneficial effect on bone and cholesterol.